Соціальні відносини на селі в давньоруські часи - Моця, О.П. (Археологія, 1999)
Розвиток східнослов'янського суспільства є часи Київської Русі суттєво вилинув на соціальне становище найбільш масового прошарку тогочасного суспільства — селянство. Во времена становления у восточных славян классового общества и существования их первого государства — Киевской Руси сформировалось крестьянство как наиболее значительный по размерам социальный страт эпохи феодализма. Решение актуальных задач в изучении жизни сельского населения перспективно лишь при комплексном использовании различных источников. В частности археологические материалы уже сейчас позволяют более обоснованно отвечать на ряд важных вопросов: иерархия поселений, проблема территориальной общины — верви, место малой и большой семьи в классовом обществе. The peasantry - the most numerous feudal social strata - emerged in the process of class formation among the Eastern Slavic tribes and throughout the lifetime of the Kyiv Rus - the first Eastern Slavic state. It should be noted, however, that only a complex approach can be successful in solving the problems related to the Kyiv Rus’ rural population. The archaeological materials are of high importance for handling the problems related to the settlements' hierarchy, territorial community (verv), and a role of a small and large families in the class differentiated society.